Back to basics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Science and the Garden. The Scientific Basis of Horticultural Practice Edited by D Ingram, D Vince Prue & PJ Gregory, Blackwell Science, 2002. 304 pp. ISBN 0632053089 GBP 19.99 Euro 30.65